Information storage and management : storing, managing, and protecting digital information in classic, virtualized, and cloud environments - Somasundaram, G.; Shrivastava, Alok.; EMC Education Services (Indianapolis, IN : John Wiley & Sons, 2012)
This book covers the components of a storage system and the different storage system models, while also offering material that explores the advances in existing technologies and the emergence of the "Cloud" as well as updates and information on new technologies.
Includes index.
oif 23/06/15
Loan
Keywords: Management information systems; Information storage